Philippines - Januard Deñola Dagdag; Aisie O. Bete; Clarinda C. Galiza (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This report discusses the extent of compliance of a higher education institution in Isabela, Philippines with the ISO 9001:2015 Quality Management System. An internal audit for clauses 4 to 9.1 of the QMS was conducted to determine the extent of QMS implementation and to identify areas of conformities, opportunities for improvement, and nonconformities. Out of the 215 findings, 177 are conformities (Cs); 25 are nonconformities (NCs); while 13 are opportunities for improvement (OFIs). The strengths of the organization include its understanding of its context, leadership of the top management, existence of planned actions to address risks and availability of almost all significant documents that support compliance and/or sustain the quality operations. Areas that need to be improved and complied include inadequate manpower for quality activities, unmet targets, and lack of control for externally provided products and services. Actions to address these findings are provided. Thus, the organization is highly recommended to carry out the corrective actions as soon as possible for continual improvement.